Jeffrey fluids heat-mass transfer analysis through porous medium by utilizing Yang-Abdel-Cattani operator - Sehra; Mehwish Shafat; Ilyas Khan (International Journal of Thermofluids)
Analyzing of mass and heat transfer through a permeable medium undergone exponential heat were studied in this article while using YAC (Yang-Abdel-Cattani) operator. The YAC operator performs the best to describe the generalized effects more convenient than other operator. By utilizing the appropriate set of dimensionless variable the governing equations of temperature, concentration and velocity distribution becomes non-dimensional. These non-dimensional partial differential equation are calculated by applying Laplace transformation. The effects of different fractional operators on fluids dynamics are examined. By the help of Mathcad tool, Various sketches were drawn to determine the physical actions of different parameters.